Abordagem initial do paciente com mielopatia aguda não compressiva - Joaquim, Andrei Fernandes [UNESP] (My University, 2007)
Acute myelopathy are characterized by spinal cord dysfunction, developing sensitive, motor and autonomic signs and symptons. Since they are relatively rare, there are some difficulties to early diagnosis and to the beginning of the treatment. So, literature was reviewed to describe the main aetiologies of acute non compressive myelopathy: 1) demyelinating diseases; 2) systemic disease; 3) parainfectious; 4) delayed radiation myelopathy; 5) vascular myelopathy; 6) idiopatic and 7) vitamin B12 deficiency. Besides, we suggest an algorithm to initial approach of these patients and further aethiologic investigation. © Copyright Morelra Jr. Editora.
Acute non compressive myelopathy
Keywords: Acute non compressive myelopathy; Differential diagnosis; Myelitis; Treatment; aciclovir; anticoagulant agent; antiinflammatory agent; azithromycin; ceftriaxone; corticosteroid; cyclophosphamide; doxycycline; ganciclovir; methylprednisolone; penicillin G; arteriovenous malformation; bacterial infection; clinical feature; cyanocobalamin deficiency; demyelinating disease; differential diagnosis; herpes simplex; Herpes simplex virus; human; multiple sclerosis; myelitis; pathophysiology; review; spinal cord disease; systemic disease